The Contribution of Geography Learning Methods to Preparedness Students to Face the Eruption of Mount Sinabung, Karo Regency - Risklarita Simanjuntak; Enok Maryani; Dede Sugandi (Budapest International Research and Critics University, 2022)
The eruption of Mount Sinabung is a natural disaster that can occur suddenly which results in damage to property and victims as well as this causes students to feel uneasy being in an area prone to the eruption of Mount Sinabung, therefore it is necessary to be prepared to deal with potential natural disasters. So that with a disaster, students do not always feel afraid. By learning geography, especially mitigation material, it is hoped that it will be able to foster student preparedness so that they are able to act appropriately in dealing with the Mount Sinabung eruption disaster. The purpose of this study was to analyze the contribution of the geography learning method to the preparedness of students. This study uses a survey method. The sample consisted of 154 students from three schools, namely SMA Negeri 1 Tigan Derket, SMA Negeri 1 Munte and SMA Muhamadiyah Kabanjahe which were located in areas prone to the eruption of Mount Sinabung and areas still affected by the eruption of Mount Sinabung. The measuring instrument used is a statement questionnaire, the data analysis technique uses descriptive inferential statistical tests with simple linear regression and correlation tests. The results showed that the contribution of the geography learning method to the preparedness of students to face the eruption of Mount Sinabung, Karo Regency was included in the low criteria. P The measuring instrument used is a statement questionnaire, the data analysis technique uses descriptive inferential statistical tests with simple linear regression and correlation tests. The results showed that the contribution of the geography learning method to the preparedness of students to face the eruption of Mount Sinabung, Karo Regency was included in the low criteria. PThis research can provide an opportunity for teachers to consider the use of appropriate geography learning methods to grow students who have preparedness.